Pharmacokinetic profiles of metamizole (dipyrone) active metabolites in goats and its residues in milk. Issue 5 (25th June 2018) - Kim, Tae Won; Łebkowska‐Wieruszewska, Beata; Sitovs, Andrejs; Poapolathep, Amnart; Owen, Helen; Lisowski, Andrzej; Abilova, Zulkyya; Giorgi, Mario
Abstract: Metamizole (dipyrone, MET) is a nonopioid analgesic drug commonly used in human and veterinary medicine. The aim of this study was to assess two major active metabolites of MET, 4‐methylaminoantipyrin (MAA) and 4‐aminoantipyrin (AA), in goat plasma after intravenous (IV) and intramuscular (IM) administration. In addition, metabolite concentration in milk was monitored after IM injection. Six healthy female goats received MET at a dose of 25 mg/kg by IV and IM routes in a crossover design study. The blood and milk samples were analyzed using HPLC coupled with ultraviolet detector and the plasma vs concentration curves analyzed by a noncompartmental model. In the goat, the MET rapidly converted into MAA and the mean maximum concentration was 183.97 μg/ml (at 0.08 hr) and 51.94 μg/ml (at 0.70 hr) after IV and IM administration, respectively. The area under the curve and mean residual time values were higher in the IM than the IV administered goats. The average concentration of AA was lower than MAA in both groups. Over 1 μg/ml of MAA was found in the milk (at 48 hr) after MET IM administration. In conclusion, IM is considered to be a better administration route in terms of its complete absorption with long persistence in the plasma. However, this therapeutic option should be considered in light of the likelihood of there being milk residue.